Probiotics, Anticipation Stress, and the Acute Immune Response to Night Shift - West, Nicholas P.; Hughes, Lily; Ramsey, Rebecca; Zhang, Ping; Martoni, Christopher J.; Leyer, Gregory J.; Cripps, Allan W.; Cox, Amanda J. (Frontiers in Immunology, 2021)
Sleep disruption are associated with chronic, low grade inflammation and may underpin a range of chronic diseases in night shift workers. aim of this study was to examine 14 days of daily probiotic supplementation on the acute response of the acute phase proteins and immune markers to sleep disruption associated with night shift work (Australia and New Zealand Clinical Trials Registry: 12617001552370). Materials and methods Individuals (mean age 41±11 yrs; 74% female) performing routine night shift were randomly assigned to a probiotic group (1×1010 colony forming units (CFU) Lactobacillus acidophilus DDS-1 or 1×1010 CFU Bifidobacterium animalis subsp. lactis UABla-12) or placebo (n= 29 per group). Participants undertook a 14-day supplementation period that coincided with a period of no night shifts followed by two consecutive night shifts. Blood samples were collected prior to the start of supplementation (V1), prior to commencing the first night shift (V2), after the first night shift (V3) and after the second night shift (V4). Serum was assessed for markers of stress (cortisol), acute phase response (C reactive protein (CRP), erythrocyte sedimentation rate, pentraxin), adhesion markers (serum E-selectin, Mucosal Vascular Addressin Cell Adhesion Molecule 1 (MAdCAM-1), and serum cytokines (interleukin (IL)-1ra, IL-1β, IL-6, tumour necrosis factor (TNF)-α, IL-10). Sleep quality was assessed with the Pittsburgh Sleep Quality Index (PSQI) and a Fitbit activity tracker. Results The groups were well balanced on key markers and the probiotic strains weres well tolerated. The 14-day supplementation period that coincided with typical night-day sleep-wake cycles leading up to night shift (V1 to V2) was associated with significant changes in the placebo group in the concentration of serum cortisol (p=0.01), pentraxin (p=0.001), MAdCAM-1 (p=0.001) and IL-1ra (p=0.03). In contrast, probiotic supplementation moderated changes in these serum markers from V1 to V2. No significant interaction effects (time by group) were observed for the serum markers prior to and after night shift work following probiotic supplementation due to the substantial changes in the serum markers that occurred during the normal sleep period from V1 to V2. Conclusions Probiotics may moderate anticipatory stress on the immune system in the lead up to night shift.